Pretend Participation: Procedural Injustices in the Madeira Hydroelectric Complex. (July 2022) - Mayer, Adam; García, María Alejandra; Castro-Diaz, Laura; Lopez, Maria Claudia; Moran, Emilio F.
Highlights: Hydropower projects are associated with a lack of participation by local population. We evaluate participation mechanisms provided by dam builders in Brazil. Negative perceptions before dam construction had little association with participation. Local population participation was rare, fleeting, and insufficient. Abstract: Energy infrastructure projects have long been associated with a lack of participation by impacted, local populations—this history is evident in the case of hydropower projects in the Global South. Ever since the World Commission on Dams' Report (WCD 2000), there has been substantive evidence, and numerous recommendations, that have called on governments, financial agencies and construction companies to increase community engagement and participation in dam construction and in their governance thereafter. Further, community groups, activists, and scholars have long articulated the need for participatory governance in energy projects. In this analysis, we evaluate participation in institutionalized mechanisms provided by dam builders—such as public meetings and negotiations—in Brazil's Madeira hydroelectric complex. We evaluate how perceptions of positive and negative impacts, among other factors, predict engagement, estimating a series of logit models based on a social survey of 673 households carried out in 2019/20. Perceptions of negative and positive impacts of the dams before construction are related to participation in the meetings promoted by dam builders. Yet our results also imply that participation was rare, fleeting, and insufficient and points to the need to ensure community engagement and governance to ensure energy justice in future dam projects in Brazil and elsewhere.